Frequency of Hypoalbuminemia in Critically ill Patients Admitted to Intensive Care Unit (Medical Forum Monthly, 2020)
Objective: Problem of hypoalbuminemia is a commonly found among those patients who are having chronic and acute medical conditions. Level of serum albumin is counted as an essential prognostic indicator. The aim of our study was to determine the frequency of hypoalbuminemia in the admitted patients who are critically ill and whose admission was in tertiary care hospital`s intensive care unit (ICU).Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of General Medicine, Liaquat National Hospital & Medical College, Karachi from July 2018 to Dec 2018.Materials and Methods: 178 patients fulfilling inclusion criteria were enrolled in this study. Patients were admitted to ICU. After shifting, blood sample was obtained through staff nurse by using 5cc BD syringe. All samples were sent to the laboratory of the hospital for assessment of albumin level to reach the outcome i.e. hypoalbuminemia. All this information was recorded a proforma.Results: Mean age of the patients was 50.66 (SD=7.97) years. There were 93(52.25%) male and 85(47.75%) female. Hypoalbuminemia`s frequency in those patients who are critically ill and whose admission was in intensive care unit (ICU) came out to be in 26.79% (48/178) patients.Conclusion: In conclusion, albumin has major role in severity of disease. Serum albumin measurement during the period of admission to the intensive care unit (ICU) could be utilized as a biomarker in order to facilitate the recognition of group of patients at high risk.